NANDA International nursing diagnoses in patients admitted to a medical clinic unit - Isabela Ubaldo; Eliane Matos; Nádia Chiodelli Salum; Juliana Balbinot Reis Girondi; Lícia Brito Shiroma (Rev Rene)
Objective: to identify nursing diagnoses, their defining characteristics and related factors, according to the NANDA-International diagnostic classification (2012-2014). Methods: a quantitative study that used as a sample 134 medical records of patients admitted to a university hospital. The analysis was based on descriptive statistics: frequency and percentage. Results: the most prevalent nursing diagnoses are in the areas of coping / stress tolerance, safety / protection and comfort. The following are the diagnoses of: risk of infection (93.8%), impaired skin integrity risk (60.4%) and anxiety (60.4%). There was a significant variation in the interpretation of the same diagnosis in relation to the defining characteristics and related factors identified. Conclusion: diagnoses presented in the research are among the most frequent in hospitalized patients with clinical intercurrences.